Amber Brown is feeling blue - Danziger, Paula, 1944-2004; Ross, Tony; Rogers, Jacqueline (New York : Scholastic, 1999)
Nine-year-old Amber Brown faces further complications because of her parents' divorce when her father plans to move back from Paris and she must decide which parent she will be with on Thanksgiving.
7.8
3-6
760
760
Keywords: Divorce -- Fiction; Parent and child -- Fiction; Divorce -- Fiction; Parent and child -- Fiction